Status of rice-fish farming and rice field fisheries in Northern Laos - Li, Youdan; Phonexay, Mali; Zhang, Zili; Li, Chenhong; Li, Jiayao; Zhang, Wenbo (Frontiers in Sustainable Food Systems, 2023)
Introduction Rice-fish farming can play an important role in increasing food production in less developed countries. The Lao People’s Democratic Republic (Laos) is one of the least developed countries in the world, and rice is the most important crop in Laos. Methods The present study conducted field surveys in 2022 in order to get a better understanding of the status of rice-fish production systems in mountainous areas in Northern Laos. Rice-fish farming was defined as one form of aquaculture in the present study, characterized by seed stocking and feed input. Rice field fisheries is mainly the harvesting of wild fish with no seed and feed input. Results We found that rice-fish production systems, including both integrated rice-fish farming and rice field fisheries, are still in resources poor status with low input levels of fertilizer and chemicals. Rice-fish farms generally have higher intensification levels in rice farming than that rice field fisheries farms. Rice-fish farms generate significantly more value output of rice than that rice field fisheries farms. Overall, rice-fish farms use land and labor more efficiently and generate higher land and labor productivity measured in value output than rice field fisheries farms. Discussion We suggest that more rice field fisheries farms can be intensified with extra seed and feed input to move to rice-fish farming to produce more aquatic products and more value output with the same rice field areas in Northern Laos.